2010 10th IEEE International Conference on Computer and Information Technology 2010
DOI: 10.1109/cit.2010.271
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Category 5e vs. Category 6 Cabling Systems for both IPv4 and IPv6 in Gigabit Ethernet

Abstract: Abstract-The performance of category 5e and 6 cabling is compared for both IPv4 and IPv6 using Gigabit Ethernet LAN. The maximum bandwidth achieved was 700Mbps and it was for IPv4 and category 5e cabling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Their findings showed that IPv4 to perform better than IPv6 by 2.7% on a peer-to-peer setup and by 4.6% on a client-server network. Similar such studies have been carried out for IPv4 and IPv6, some evaluating over different OSs [3] whereas others over cabling systems [4] and wireless systems [5]. An earlier work evaluated IP performance using open source OSs [6].…”
Section: Related Workmentioning
confidence: 83%
See 2 more Smart Citations
“…Their findings showed that IPv4 to perform better than IPv6 by 2.7% on a peer-to-peer setup and by 4.6% on a client-server network. Similar such studies have been carried out for IPv4 and IPv6, some evaluating over different OSs [3] whereas others over cabling systems [4] and wireless systems [5]. An earlier work evaluated IP performance using open source OSs [6].…”
Section: Related Workmentioning
confidence: 83%
“…Windows 7 connected to Windows Server 2008) using a Category 6 crossover cable. The separation between the client and server was set to 1 meter as suggested by network researchers [3][4][5]. We use the same connection for linking two Linux machines (Ubuntu 10.04 and Red Hat Server 5.5).…”
Section: A Testbed Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Chris Manford et al [8] In 2010, Burjiz K. Soorty et al [9] evaluated the performance of IPv4 and IPv6 over different cabling systems. Two commonly used industry cabling systems namely Category 5e and Category 6 were tested for IP performance over a Gigabit Ethernet LAN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that UDP achieved higher throughput with Category 5e cabling than Category 6 thereby making Category 5e a much suitable preference for data traffic. Packet delay was found to be lower with Category 6 than Category 5e due to Category 6 providing about 12 dB (or 16 times) better Signal-to-Noise Ratio than Category 5e over a wide frequency range [9] thus making Category 6 a much viable preference for delay-sensitive traffic (e.g. VoIP).…”
Section: Literature Reviewmentioning
confidence: 99%